2023
DOI: 10.1038/s41598-023-31254-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propolis on mood, quality of life, and metabolic profiles in subjects with metabolic syndrome: a randomized clinical trial

Abstract: Metabolic syndrome (MeS) is a common multifaceted disorder. Plants contain antioxidant bioactive compounds, which are beneficial to improve the health condition of patients with MeS. Propolis is a hive natural product that is composed of various constituent. We aimed to assess the effects of Iranian propolis as a natural and safe agent on indicators of MeS, quality of life and mood status in individuals with MeS. In total, 66 interested eligible patients recruited to the present study. Participants were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Metabolic disorders encompass a spectrum of conditions that disrupt normal metabolic processes, resulting in various health problems, including type 2 diabetes mellitus (T2DM), obesity, and metabolic syndrome (MetS). 1 , 2 Furthermore, the pathologies of metabolic diseases are intricate and multifactorial, and elevate the risk for cardiovascular disease (CVD). 3 In their recent article, Saeedi et al reported that 9.3% of the global population (463 million people) was estimated to suffer DM, and this number is expected to increase to 10.2% (578 million) by 2030 and further to 10.9% by 2045.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic disorders encompass a spectrum of conditions that disrupt normal metabolic processes, resulting in various health problems, including type 2 diabetes mellitus (T2DM), obesity, and metabolic syndrome (MetS). 1 , 2 Furthermore, the pathologies of metabolic diseases are intricate and multifactorial, and elevate the risk for cardiovascular disease (CVD). 3 In their recent article, Saeedi et al reported that 9.3% of the global population (463 million people) was estimated to suffer DM, and this number is expected to increase to 10.2% (578 million) by 2030 and further to 10.9% by 2045.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have evaluated the efficacy of plant-based or herbal preparations for metabolic disorders and their risk factors. 2 , 16 , 19 , 20 , 23 , 24 Furthermore, the mechanism of actions of bioactive compounds on metabolic biomarkers has also been reported. 25 , 26 However, their potential on how those bioactive compounds exhibit multiple and synergistic effects on metabolic and immune systems is not thoroughly discussed yet.…”
Section: Introductionmentioning
confidence: 99%